Rainwater harvesting and integrated development of agri-horti-livestock-cumpisciculture in high altitudes for livelihood of Tribal farmers - DAS, ANUP; MUNDA, G C; AZAD THAKUR, N S; YADAV, R K; GHOSH, P K; NGACHAN, S V; BUJARBARUAH, K M; LAL, B; DAS, S K; MAHAPATRA, B K; ISLAM, M; DUTTA, K K (The Indian Journal of Agricultural Sciences, 2014)
Participatory rainwater harvesting for promoting integrated development of agri-horti-livestock-cum-pisciculture was implemented during 2004-2008 at high altitude (> 1500m MSL) areas of Mawlangkhar village, West Khasi Hills district, Meghalaya in a watershed approach to assess and refine improved package of practices integrating crops, fruits, vegetables, fish and animal production for higher productivity and income. Soil and water conservation measures like construction and renovation of ponds, jalkund- a micro rainwater harvesting structure on hilltops, bench and half moon terraces were developed with the active participation of the local peoples. The quantum of water harvested at one point of time during monsoon season through two ponds in community lands (2.69 million litre water), two ponds in individual farmer’s land (1.2 million litre water) and 15 jalkunds (0.45 million litre) on hill tops estimated to be about 4.3 million litre, was utilized for multiple purposes including irrigation, pisciculture, livestocks and domestic purpose. The cost of water harvesting in community pond was computed at ₹ 12/1000 litre (L) and for jalkund ₹ 82/1000 litre considering the lives of pond and jalkund for at least 20 and 3 years, respectively. Impact analysis revealed that the productivity has gone up by 30–40% in potato and 45-50 % in rice with the introduction of improved package of practices for various crops, availability of irrigation water and integration of different components. Farmers are now able to get about ₹ 2 440/month from community dairy unit and the individual farmer’s income from piggery unit increased substantially which ranged from ₹ 8 465 to 16 654/year. Besides, farmers are earning a substantial income (₹ 10 000/annum from community pond) from composite pisciculuture. Therefore, integrated watershed programme could be considered as a successful model for high altitude areas of North East India and similar other ecosystems for livelihood improvement of resource poor tribal farmers.